2019
DOI: 10.1186/s12864-019-6173-4
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and transcriptome analysis reveal molecular mechanism in Salvia miltiorrhiza leaves of near-isogenic male fertile lines and male sterile lines

Abstract: BackgroundOur previous study finds that male sterility in Salvia miltiorrhiza could result in stunted growth and reduced biomass, but their molecular mechanisms have not yet been revealed. In this article, we investigate the underlying mechanism of male sterility and its impact on plant growth and metabolic yield by using physiological analysis and mRNA sequencing (RNA-Seq).ResultsIn this study, transcriptomic and physiological analysis were performed to identify the mechanism of male sterility in mutants and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…Thus, the analysis of the origin of S. miltiorrhiza sterility will help people to cultivate male sterile lines, and provide germplasm resources for artificial crossbreeding in the future. A previous study analyzed physiological characteristics and metabolic differences in leaves of the sterile line of S. miltiorrhiza [ 24 ]. In the hybrid offspring of S. miltiorrhiza and S. miltiorrhiza f. alba , male sterility was caused by abnormal microgametogenesis, and key genes were initially screened through a comparative transcriptome analysis [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the analysis of the origin of S. miltiorrhiza sterility will help people to cultivate male sterile lines, and provide germplasm resources for artificial crossbreeding in the future. A previous study analyzed physiological characteristics and metabolic differences in leaves of the sterile line of S. miltiorrhiza [ 24 ]. In the hybrid offspring of S. miltiorrhiza and S. miltiorrhiza f. alba , male sterility was caused by abnormal microgametogenesis, and key genes were initially screened through a comparative transcriptome analysis [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14][15] Through continuous backcross and testcross in 2006-2009, we found that S. miltiorrhiza male sterility belonged to the GMS type. 16,17 Male sterility plays a signicant role in hybrid breeding, and it is a good way to generate stronger plants and to produce high-quality F1 hybrid seeds. 18 The GMS is a very stable genetic system that includes fertile (Ms f Ms) and sterile (MsMs) plants that segregate in a 1 : 1 ratio.…”
Section: Introductionmentioning
confidence: 99%